2018
DOI: 10.1089/fpd.2017.2415
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Vibrio parahaemolyticus Associated with Consumption of Raw Oysters in Canada, 2015

Abstract: There has been a steady increase in illness incidence of Vibrio parahaemolyticus (Vp). The majority of illnesses are associated with consumption of raw oysters. In the summer of 2015, Canada experienced the largest outbreak associated with the consumption of raw oysters harvested from British Columbia (BC) coastal waters. Case investigation of laboratory-confirmed cases was conducted to collect information on exposures and to assist traceback. Investigations at processors and oyster sampling were conducted. Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 7 publications
0
28
0
Order By: Relevance
“…Oysters may contain foodborne pathogens, such as Vibrio parahaemolyticus. Vibrio parahaemolyticus , a foodborne pathogen that is naturally present in the aquatic marine environment, can contaminate the surface or enter the tissues of oysters (Baker‐Austin et al., 2018; Taylor, Cheng, et al., 2018). Vibrio parahaemolyticus , a Gram‐negative bacterium, was first isolated in 1950, and has become a pathogen of global concern following the appearance of the first pandemic O3:K6 strain in 1996 (Nair et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oysters may contain foodborne pathogens, such as Vibrio parahaemolyticus. Vibrio parahaemolyticus , a foodborne pathogen that is naturally present in the aquatic marine environment, can contaminate the surface or enter the tissues of oysters (Baker‐Austin et al., 2018; Taylor, Cheng, et al., 2018). Vibrio parahaemolyticus , a Gram‐negative bacterium, was first isolated in 1950, and has become a pathogen of global concern following the appearance of the first pandemic O3:K6 strain in 1996 (Nair et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the risk caused by the presence of V. parahaemolyticus in oysters can be easily reduced or eliminated by adequate cooking. However, in many cases, V. parahaemolyticus infection occurs because of the consumption of raw or undercooked oysters that may be contaminated by V. parahaemolyticus (Huang, Hwang, Huang, Wu, & Hsiao, 2018; Sobrinho, Destro, Franco, & Landgraf, 2014; Taylor, Cheng, et al., 2018). In a report, even with consumer who reported eating only thoroughly cooked (grilled, stewed, or fried) oysters were as likely to become ill as those who ate raw oysters due to the failure of cooking (McDonnell et al., 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic clone has the typical tdh + trh − , toxRS/new + , orf8 +/− genotype, which is identified by Group-specific PCR (GS-PCR) that detects the sequence variation in toxRS gene (toxRS/new) [14,15]. The burden of V. parahaemolyticus diarrhoea is very high in Asian countries [16][17][18] and the outbreaks are related to raw shellfish consumption in the United States and Canada [19,20]. In addition, sporadic outbreaks have been reported in coastal Europe [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note, however, that only the member of this pathogen, which had virulence factors ( trh and/or tdh ), is considered to be pathogenic (Raghunath, ). Recently, 82 cases of V. parahaemolyticus infection linked to consumption of raw oysters were reported in 2015 in Canada (Taylor, Cheng, Sharma, & Bitzikos, ). In China, Chen, Zhang, Qi, Zhou, and Zhang () reported that 38% of 71 foodborne outbreaks caused by V. parahaemolyticus between 2010 and 2014 were linked to aquatic products (Chen et al., ).…”
Section: Introductionmentioning
confidence: 99%